Free Speech Rhetoric and Normalizing Violence: Setting Higher Standards for University Guest Speaker Policies - McDonald, Madison (Atlantis, 2020)
In response to recent protests against controversial guest speakers, many Canadian universities have implemented new policies that conflate academic freedom and freedom of speech. The resultant free speech policies often protect speakers regardless of the content of their speech; this paper discusses the importance of barring speech that normalizes acts of harm.